1996
DOI: 10.1182/blood.v87.7.2805.bloodjournal8772805
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces the rapid tyrosine phosphorylation of the mitogen-activated protein kinases erk-1 and p38 in cultured human vascular endothelial cells requiring the presence of soluble CD14

Abstract: Human vascular endothelial cells (HUVECs), which do not display the lipopolysaccharide (LPS) receptor CD14, were examined for protein tyrosine phosphorylation after LPS stimulation in the presence and absence of soluble CD14 (sCD14). By phosphotyrosine Western blotting and immunocomplex kinase assays we show that LPS was capable of inducing in these cells rapid protein tyrosine phosphorylation and kinase activation of two members of the mitogen-activated protein kinase (MAPK) family erk-1 and the newly discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 45 publications
(1 reference statement)
1
28
1
1
Order By: Relevance
“…We found that the effect of LPS on MAPK phosphorylation was time dependent, as was the ability of acetate treatment to reduce LPS-induced p38 and JNK phosphorylation. LPS increased phosphorylated p38 at 4 h and phosphorylated JNK at 2 and 4 h, whereas acetate treatment reduced phosphorylated p38 and JNK only at 2 h, but not 4 h. We did not observe an increase in MAPK activation at 0.5 or 1 h unlike other studies (Schumann et al 1996;Kraatz et al 1998). However, this may be because of our using a lower concentration of LPS or may demonstrate a cell-type-specific response.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We found that the effect of LPS on MAPK phosphorylation was time dependent, as was the ability of acetate treatment to reduce LPS-induced p38 and JNK phosphorylation. LPS increased phosphorylated p38 at 4 h and phosphorylated JNK at 2 and 4 h, whereas acetate treatment reduced phosphorylated p38 and JNK only at 2 h, but not 4 h. We did not observe an increase in MAPK activation at 0.5 or 1 h unlike other studies (Schumann et al 1996;Kraatz et al 1998). However, this may be because of our using a lower concentration of LPS or may demonstrate a cell-type-specific response.…”
Section: Discussioncontrasting
confidence: 87%
“…Acetate treatment and LPS alter MAPK phosphorylation in a time-dependent manner in BV-2 microglia Because MAPK signaling can be inhibited by the acetylation of MAPK phosphatase-1, which induces deacetylation and deactivation of MAPK (Cao et al 2008), we measured the effects of acetate treatment on LPS-induced MAPK phosphorylation at 0.5, 1, 2, and 4 h. The rationale for including multiple time points is that other studies reported MAPK activation by LPS at much earlier time points than 4 h (Schumann et al 1996;Kraatz et al 1998). Whole cell lysates were used for western blot analysis, and phosphorylated p38, p38, phosphorylated JNK, JNK, phosphorylated ERK1/2, and ERK1/2 were detected as protein bands corresponding to the molecular weights of 38, 38, 46, 54 and 46, and 42 and 46 kDa, respectively (Fig.…”
Section: Acetate Treatment Reverses Lps-induced H3k9 Hypoacetylation mentioning
confidence: 99%
“…The involvement of both PTK and p38 MAPK in iLpsR expression induced by LPS is consistent with the involvement of these two families of kinases in other LPS-induced eÂĄects, such as the production of inÂŁammatory cytokines in monocytes [20], and the expression of the cell surface adhesion molecule-1 by human vascular endothelial cells [21]. It is noteworthy that the requirement of these kinases for LPS responses seems unrelated to the presence of the membrane form of CD14^the putative LPS receptorĆ” hich is present in the former, but absent in the latter cell type, and also absent in the unstimulated BMC used in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…In macrophages it has been shown that LPS and other bacterial components can induce the activation of all three pathways (101). The p38 and ERK pathways are also activated by LPS in human umbilical vein endothelial cells in the presence of soluble CD14 (102). Both of these pathways are also activated by LPS in macrophages to stimulate the expression of the cyclooxygenase gene (103).…”
Section: Signal Transductionmentioning
confidence: 99%